Artificial Intelligence Methods in Predicting the Productivity of Project Teams: Transhumanism and Experience in Practical Research - Fedotova, Marina; Kozlova, Elena; Yin Bìn (Տիգրան Մեծ)
The article considers issues related to the use of artificial intelligence methods in the technoscience concept while moving from personnel management to human resource management using artificial intelligence elements. Authors considerthe development of human resources at the expense of cognitive-communicative resources of personnel in specific (transformed) conditions of consciousness when a syn-ergy of neurocognitively enhanced human capabilities and artificial intelligence occurs. Such situations are considered in predicting the productivity of project teamwork, characterized by various aspects: organizational, cognitive-communicative, socio-psychological, etc. It is analyzed a specific example of predictive analytics related to the assessment of future results of newly created teams (shift teams) and results that are corrected based on already existing teams (V. K. Finn‟s DSM-method of automatic hypotheses generation, as a way to organize knowledge using the non-Aristotelian structureof concepts, 2009). Some difficulties of using the shift form of labour organization are considered. The methodology for predicting the teams‟ assessment is based on the results of express diagnostics of their work on specific test cases and the general database of characteristics and results already existing successful and unsuccessful teams.
Keywords: Philosophy of economics